Fuzzy Measure and Probability Distributions Distorted Probabilities. - Narukawa, Y.
This work studies fuzzy measures and their application to data modeling. We focus on the particular case when fuzzy measures are distorted probabilities. We analyze their properties and introduce a new family of measures (m-dimensional distorted probabilities). The work finishes with the application of two dimensional distorted probabilities to a modeling problem. Results of the application of such fuzzy measure to data modeling using Choquet integral are discussed
Keywords: Choquet integral; Data modeling; Distorted probabilities; Fuzzy measure; Probability distribution